Pengaruh Manajemen Pakan Terhadap Kualitas Eksternal Telur Pada Beberapa Peternakan Ayam Ras Petelur Di Pulau Ambon - Lopulalan, Melissa; Ralahalu, Tabita N; Horhorouw, Wisye M (Universitas Pattimura, 2024)
This study aimed to determine the effect of feed management on the external quality of eggs across several laying hens farms situated on Ambon Island. Sampling was conducted at three distinct locations: Suli village, Hulung hamlet, and Taeno hamlet. External quality assessment of eggs was carried out at the Laboratory of Biochemistry and Animal Nutrition, Department of Animal Husbandry, Faculty of Agriculture, Unpatti, while proximate analysis of feed was performed at the Laboratory of the research center for biological resources, biotechnology, research institute and community service, IPB. The research employed combination of survey methods and interviews. Egg sampling at the farm locations occurred four times weekly, with measurements for egg weight, egg index, and egg shape. Egg weight and egg index were analyzed using t-test method, while egg shape was evaluated using the Chi-Square test. The average egg weight weight at Suli village farm was 54.29 g, at Hulung hamlet farm was 63.24 g and at the Taeno hamlet farm was 64.04 g. Correspondingly, the average egg index was 79.96% in Suli village, 79.18% in Hulung hamlet, and 78.71% in Taeno hamlet. The egg shape index across the three farm locations was 61.50. Results indicated a significant effect 0f feed across all three laying hen farm locations on egg weight and egg index, with observed correlations between the provided feed and egg shape.